Case Report: Treating Atrial Fibrillation with the Neubie Direct Current Electrical Stimulation - Ennis R; Husted C (Medical Devices: Evidence and Research, 2025)
Richard Ennis,1,2,* Cynthia Husted2,3,* 1Whidbey Island Rolfing, Freeland, WA, USA; 2Science and Spirit Institute, Greenbank, WA, USA; 3Integrative Functional Medicine, Freeland, WA, USA*These authors contributed equally to this workCorrespondence: Richard Ennis, Science and Spirit Institute, P.O. Box 11, Greenbank, WA, 98253, USA, Tel +1-650-868-3357, Email richennis1@gmail.comIntroduction: A novel Neuro-Bio-Electric-Stimulation device (Neubie, Neufit, Austin, Texas, USA) using Direct Current (DC) has been used to treat various neurological conditions (ALS, MS, peripheral neuropathy, chronic pain) and functional limitations such as limited range of motion. One method, called the Master Reset Protocol, is thought to stimulate the vagus nerve system, impacting heart rate, digestion and other vital systems.Purpose: We used the Master Reset Protocol on a subject experiencing paroxysmal Atrial Fibrillation (AFib) to assess whether this treatment might be effective in reversing a cardiac arrhythmia.Subject and Methods: A single subject is reported in this Case Report. The subject is a 62-year-old healthy, athletic male, 6′ 2″ tall, 165 lbs. with a good diet and is not obese nor has other exacerbating underlying conditions related to heart disease. The subject experiences arrhythmia approximately 1– 2 times per month lasting generally 3 or more days per the subject. The Master Reset Method was initiated within 12 hours of arrhythmia onset, and arrhythmia before and after treatment was confirmed through subject observation and confirmed with pulse readings. A total of ten treatments were conducted over 7 months.Results: Reversal of arrhythmia was confirmed during or within 24 hours of treatment with DC application for all 10 treatments (100%). Two of the more severe cases of AFib required two treatments on the same day with confirmed reversal of AFib.Conclusion: Treatment with Direct Current suggests a good correlation with reversal of arrhythmia. Further studies are planned to determine if similar, regular, treatments can be effective in preventing arrhythmia.Keywords: AFib, cardiac arrhythmia, vagus nerve, direct current, electrical stimulation